Efficacy and tolerability of selective serotonin reuptake inhibitors compared with tricyclic antidepressants in depression treated in primary care: systematic review and meta-analysis. Issue 7397 (10th May 2003) - MacGillivray, Steve; Arroll, Bruce; Hatcher, Simon; Ogston, Simon; Reid, Ian; Sullivan, Frank; Williams, Brian; Crombie, Iain
Abstract: Objective: To compare the efficacy and tolerability of tricyclic antidepressants with selective serotonin reuptake inhibitors in depression in primary care. Design: Systematic review and meta-analysis of randomised controlled trials. Data sources: Register of the Cochrane Collaboration's depression, anxiety, and neurosis group. Reference lists of initial studies and other relevant review papers. Selected authors and experts. Selection of studies: Studies had to meet minimum requirements on: adequacy of sample size, adequate allocation concealment, clear description of treatment, representative source of subjects, use of diagnostic criteria or clear specification of inclusion criteria, details regarding number and reasons for withdrawal by group, and outcome measures described clearly or use of validated instruments. Main outcome measures: Standardised mean difference of final mean depression scores and relative risk of response when using the clinical global impression score. Relative risk of withdrawing from treatment at any time, and the number withdrawing due to side effects. Results: 11 studies (2951 participants) compared a selective serotonin reuptake inhibitor with a tricyclic antidepressant. Efficacy between selective serotonin reuptake inhibitors and tricyclics did not differ significantly (standardised weighted mean difference, fixed effects 0.07, 95% confidence interval −0.02 to 0.15; z=1.59, P<0.11). Significantly more patients receiving a tricyclic withdrew from treatment (relative risk 0.78, 95% confidence interval 0.68 to 0.90; z=3.37, P<0.0007) and withdrew specifically because of side effects (0.73, 0.60 to 0.88; z=3.24, P<0.001). Most studies included were small and supported by commercial funding. Many studies were of low methodological quality or did not present adequate data for analysis, or both, and were of short duration, typically six to eight weeks. Conclusion: The evidence on the relative efficacy of selective serotonin reuptake inhibitors and tricyclic antidepressants in primary care is sparse and of variable quality. The study setting is likely to be an important factor in assessing the efficacy and tolerability of treatment with antidepressant drugs.